Effect of Lemongrass Essential Oil on Gelatin Edible Film: Water Vapor Transmission, Gelation, and Chemical Structure - Fahrullah, Fahrullah; Rosida, Abidatur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Edible film constitutes a thin layer that is capable of biodegradation and is therefore considered safe for consumption, thus providing a more environmentally friendly alternative to conventional plastics. The objective of the present study was to ascertain the impact of lemongrass essential oil incorporation on the water vapour transmission rate, gelation time and chemical structure of gelatin edible film. The present study employed a randomised experiment, incorporating 3 distinct treatments and 3 replicates for each treatment. The treatments comprised three groups: P1, which did not include the addition of lemongrass essential oil; P2, which incorporated the addition of lemongrass essential oil at a rate of 4%; and P3, which incorporated the addition of lemongrass essential oil at a rate of 8%. The findings demonstrated that the incorporation of lemongrass essential oil did not exert a substantial influence on the WVTR value (P > 0.05), with the mean value remaining within the parameters stipulated by the Japanese Industrial Standard. Conversely, the gelation time exhibited a significant increase (P<0.01) with rising lemongrass oil concentrations, attributable to the disruption of gelatin intermolecular bonds. FTIR analysis demonstrated interactions between the film components, with an increase in the intensity of certain functional groups indicating alterations in the chemical structure, particularly at a concentration of 4%, which resulted in optimal interactions without compromising the gelatin protein structure. The study concluded that the incorporation of lemongrass oil at concentrations up to 4% yielded optimal outcomes in enhancing the flexibility and antimicrobial properties of edible film, without compromising its structural stability.